Factors Affecting Willingness to Use Hospice in Racially/Ethnically Diverse Older Men and Women. (September 2016) - Park, Nan Sook; Jang, Yuri; Ko, Jung Eun; Chiriboga, David A.
Racial/ethnic minorities tend to underutilize hospice services. Guided by Andersen behavioral health model, the purpose of this study was to explore the predictors of the willingness to use hospice services in racially/ethnically diverse older men and women. Data were drawn from the Survey of Older Floridians: 504 non-Hispanic whites, 360 African Americans, 328 Cuban Americans, and 241 non-Cuban Hispanics. In each group, logistic regression models of the willingness to use hospice were estimated. A greater likelihood of willingness was observed among younger non-Hispanic whites and among African Americans with fewer functional disabilities. In non-Cuban Hispanics, English proficiency increased the willingness by 3.1 times. Findings of the study identified group-specific factors contributing to the willingness to use hospice services and hold implications for tailored intervention programs.